Stapled versus hand-sewn: A prospective emergency surgery study. An American Association for the Surgery of Trauma multi-institutional study. Issue 3 (March 2017) - Bruns, Brandon Robert; Morris, David S.; Zielinski, Martin; Mowery, Nathan T.; Miller, Preston R.; Arnold, Kristen; Phelan, Herb A.; Murry, Jason; Turay, David; Fam, John; Oh, John S.; Gunter, Oliver L.; et al.
Abstract : BACKGROUND: Data from the trauma patient population suggests handsewn (HS) anastomoses are superior to stapled (ST). A recent retrospective study in emergency general surgery (EGS) patients had similar findings. The aim of the current study was to evaluate HS and ST anastomoses in EGS patients undergoing urgent/emergent operations. METHODS: The study was sponsored by the American Association for the Surgery of Trauma Multi-Institutional Studies Committee. Patients undergoing urgent/emergent bowel resection for EGS pathology were prospectively enrolled from July 22, 2013 to December 31, 2015. Patients were grouped by HS/ST anastomoses, and variables were collected. The primary outcome was anastomotic failure. Similar to other studies, anastomotic failure was evaluated at the anastomosis level. Multivariable logistic regression was performed controlling for age and risk factors for anastomotic failure. RESULTS: Fifteen institutions enrolled a total of 595 patients with 649 anastomoses (253 HS and 396 ST). Mean age was 61 years, 51% were men, 7% overall mortality. Age and sex were the same between groups. The overall anastomotic failure rate was 12.5%. The HS group had higher lactate, lower albumin, and were more likely to be on vasopressors. Hospital and intensive care unit days, as well as mortality, were greater in the HS group. Anastomotic failure rates and operative time were equivalent for HS and ST. On multivariate regression, the presence of contamination at initial resection (odds ratio, 1.965; 95% confidence interval, 1.183–3.264) and the patient being managed with open abdomen (odds ratio, 2.529; 95% confidence interval, 1.492–4.286) were independently associated with anastomotic failure, while the type of anastomosis was not. CONCLUSION: EGS patients requiring bowel resection and anastomosis are at high risk for anastomotic failure. The current study illustrates an apparent bias among acute care surgeons to perform HS techniques in higher-risk patients. Despite the individualized application of technique for differing patient populations, the risk of anastomotic failure was equivalent when comparing HS and ST anastomoses. LEVEL OF EVIDENCE: Therapeutic study, level II.